A Digitally Enhanced Ethnography for Craft Action and Process Understanding - Xenophon Zabulis; Partarakis Nikolaos; Vasiliki Manikaki; Ioanna Demeridou; Arnaud Dubois; Inés Moreno; Valentina Bartalesi; Nicolò Pratelli; Carlo Meghini; Sotiris Manitsaris; Gavriela Senteri (Applied Sciences)
Traditional ethnographic methods have long been employed to study craft practices, yet they often fall short of capturing the full depth of embodied knowledge, material interactions, and procedural workflows inherent in craftsmanship. This paper introduces a digitally enhanced ethnographic framework that integrates Motion Capture, 3D scanning, audiovisual documentation, and semantic knowledge representation to document both the tangible and dynamic aspects of craft processes. By distinguishing between endurant (tools, materials, objects) and perdurant (actions, events, transformations) entities, we propose a structured methodology for analyzing craft gestures, material behaviors, and production workflows. The study applies this proposed framework to eight European craft traditions—including glassblowing, tapestry weaving, woodcarving, porcelain pottery, marble carving, silversmithing, clay pottery, and textile weaving—demonstrating the adaptability of digital ethnographic tools across disciplines. Through a combination of multimodal data acquisition and expert-driven annotation, we present a comprehensive model for craft documentation that enhances the preservation, education, and analysis of artisanal knowledge. This research contributes to the ongoing evolution of ethnographic methods by bridging digital technology with Cultural Heritage studies, offering a robust framework for understanding the mechanics and meanings of craft practices.